Janice Vancleave's Wild, Wacky, And Weird Physics Experiments - Janice Pratt VanCleave
In a series of fun and involving hands-on physics experiments, kids learn how a flashlight works, what materials are attracted to a magnet, how a heavy ship floats, how gravity affects the shape of soap bubbles, and how and why heavy things fall faster than lighter things. They will also determine and demonstrate the attraction between unlike charges and the repulsion between like charges, the part of a magnet that has the strongest attracting ability, and how levers, pulleys, wedges, and inclined planes work and how they save energy and labor. Featuring color illustrations and safe, simple step-by-step instructions, Janice VanCleave again shows just how much fun science can be.